Analysis of High School Students’ Critical Thinking Skills Profile According to Ennis Indicators - Leni Dwi Septiany; Rinie Pratiwi Puspitawati; Endang Susantini; Mohammad Budiyanto; Tarzan Purnomo; Eko Hariyono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to identify the profile of senior high school students' critical thinking skills in ecosystem material on several critical thinking indicators compiled by Ennis. Method: This research uses quantitative descriptive methods. The research used six essay questions prepared to analyze students' thinking skills based on several indicators compiled by Ennis. The population in this study were all high school students at one of the senior high schools in West Nusa Tenggara, with the sample being class X students with a total of 60 students. Results: Based on research findings, it is known that the skills of the students in the sample are divided into three categories, namely very low, low, and moderate. Half of the sample size is in the very low category. At the same time, the rest is divided into the low and moderate categories, where a small number of students belong to the moderate category. Novelty: The novelty of this research is to explore the level of students' critical thinking skills using indicators compiled by Ennis. These results will provide an overall understanding of students' critical thinking skills, which teachers can use as a basis for designing learning designs to train students' critical thinking skills to reach the high and very high categories.